Stochastic resonance in a nonlinear mechanical vibration isolation system - Lu, Zeqi; Chen, Li-Qun; Brennan, Michael J. [UNESP]; Yang, Tiejun; Ding, Hu; Liu, Zhigang (Elsevier, 2016)
This paper concerns the effect that a stochastic resonance can have on a vibration isolation system. Rather than reducing the transmitted force, it is shown that it is possible to significantly mask the component of the force transmitted though the isolator, when the system is excited harmonically. This can be achieved by adding a very low intensity of random noise to the harmonic excitation force. The nonlinear mechanical vibration isolation system used in the study consists of a vertical linear spring in parallel with two horizontal springs, which are configured so that the potential energy of the system has a double-well. Prior to the analytical and numerical study, an experiment to demonstrate stochastic resonance in a mechanical system is described.
Keywords: Double-well; Nonlinear isolation; SNR of transmitted force; Stochastic resonance